FURNITURE SALES SYSTEM INAMEL FURNITURE - Jemmy Meikel Mandagi; Sahni D.P, SKom, MM Sahni D.P, SKom, MM (Jurnal Sistem Informasi, 2000)
Computerized systems furniture sales service on the "AMELFURNITURE" This will be very useful in the process of selling furniture. With the use of this system, the process of selling furniture on "AMELFURNITURE" would be better, orderly, effective and efficient. Errors that occur in Furniture sales process will be minimal anticipated to generate quality information for those who need it.